Relevance of Nepal’s 1975 Zone of Peace Proposal in Contemporary Geopolitics (The Shivapuri Journal, 2025)
Seventy years after the inception of the Five Principles of Peaceful Coexistence (FPPC) - mutual respect for sovereignty, non-aggression, non-interference, equality, and peaceful coexistence-this article revisits Nepal’s 1975 Zone of Peace (ZoP) proposal in the context of contemporary geopolitical dynamics.  Rooted in FPPC and Nepal’s commitment to non-alignment, the ZoP initiative sought to safeguard Nepal’s sovereignty amid Cold War tensions, rising neocolonialism, and the strategic pressures posed by neighboring powers India and China. Despite garnering widespread international support, the ZoP faced resistance from India due to historicaltreaties, security concerns, and strategic interests, ultimately hindering its implementation. This article examines the historical imperatives, international responses, and subsequent developments surrounding Nepal’s ZoP proposal. It highlights how the initiative underscored Nepal’s aspiration for neutrality and stability in an increasingly polarized world. Drawing parallels with evolving geopolitical realities-such as the U.S. Indo-Pacific strategy, China’s Belt and Road. Initiative, and India’s regional ambitions-the article evaluates the continued relevance of FPPC and the ZoP in Nepal’s foreign policy framework.  Addressing the challenges posed by India’s strategic apprehensions, the article proposes a way forward rooted in transparent diplomacy, economic collaboration, and public engagement. It emphasizes the importance of  Nepal positioning itself as a stabilizing force in South Asia, leveraging neutrality to foster regional security and economic opportunities. The article concludes by affirming the enduring significance of FPPC and the ZoP as guiding principles for Nepal’s sovereignty and diplomatic strategy.  It calls for further research into the adaptability of such frameworks in conflict-prone regions, providing insights into their role in fostering peace, stability, and cooperation in an increasingly complex global order. This analysis underscores the need for small states like Nepal to prioritize peaceful coexistence to navigate shifting global power dynamics effectively.